2014
DOI: 10.1111/jphp.12281
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human cytochrome P450 isozymes involved in the metabolism of naftopidil enantiomers in vitro

Abstract: Both R(+)-NAF and S(-)-NAF are metabolized to three metabolites in HLMs. CYP2C9 plays the most important role in the demethylation and hydroxylation of both NAF enantiomers, CYP2C19 is another major CYP isoform that is involved in R(+)-NAF metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Naftopidil in racemic form was provided by Trimax Bio Sciences Ltd. The drug used in clinical practice is the racemate 23 of the free base. Purity of the compound was confirmed by powder X-ray diffraction (PXRD) and differential scanning calorimetry (DSC).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Naftopidil in racemic form was provided by Trimax Bio Sciences Ltd. The drug used in clinical practice is the racemate 23 of the free base. Purity of the compound was confirmed by powder X-ray diffraction (PXRD) and differential scanning calorimetry (DSC).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The liver microsomes, plasma protein binding and a Caco-2 cell monolayer were simultaneously used for studying the mechanism of in vivo drug disposition differences of the chiral drug phencynonate 29,30 . Our results showed that there were significant differences observed in the metabolic stabilities of the two enantiomers of phencynonate in rat liver microsomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identified three phase I metabolites and two phase II conjugations in rat plasma containing NAF glucuronides and hydroxyl-NAF glucuronides ( Niebch et al, 1991 ; Li et al, 2006 ). Three phase I metabolites, NHN, PHN, and DMN, required catalytic activity by CYP2C9 and CYP2C19 ( Zhu et al, 2014 ). It was not possible to quantify levels of these metabolites, so contributions of CYP450s and UGTs to the metabolism of NAF remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Three phase I metabolites [(phenyl) hydroxy-NAF (PHN), (naphthyl) hydroxy-NAF (NHN), and O -desmethyl-NAF (DMN)] and two phase II metabolites (NAF and NHN glucuronide conjugates) were identified ( Niebch et al, 1991 ; Li et al, 2006 ). Phase I metabolism of NAF is mediated by cytochrome P450 enzymes (CYP) 2C9 and CYP2C19 ( Zhu et al, 2014 ). Our previous studies indicated the stereoselective pharmacokinetic profiles of NAF enantiomers.…”
Section: Introductionmentioning
confidence: 99%